Colleters on the inflorescence axis of croton glandulosus (euphorbiaceae): structural and functional characterization - Machado, Silvia R. [UNESP]; Paleari, Lucia M. [UNESP]; Paiva, Elder A. S.; Rodrigues, Tatiane M. [UNESP] (Univ Chicago Press, 2015)
Premise of research. Croton glandulosus L. is a ruderal annual species of Euphorbiaceae native to the American tropics and widespread in urban and rural areas in Brazil. We investigated the structure, histochemistry, and ultrastructure of glands on the inflorescence axis of C. glandulosus to explore the relationship between their structure and function.Methodology. Reproductive apexes were prepared according to standard methods for plant anatomy, SEM., and TEM. Histochemical tests were performed using fresh material.Pivotal results. Mature glands are bowling pin shaped and are differentiated into a single-layered secretory epidermis arranged radially around a parenchymatous central axis supplied with xylem. In the neck region of the glands, the epidermal cells present structural components typical of lipophilic secretion, whereas the parenchyma cells are specialized in the production of hydrophilic compounds. The resinous secretion is released by cuticle pores occurring exclusively on the tip of the gland.Conclusions, This is the first report of the occurrence of colleters on the inflorescences of a Croton species. Our observations clearly indicate that glands on the inflorescence axis of C. glandulosus are resin-secreting colleters that may have important protective functions.
Keywords: Anatomy; Colleters; Croton glandulosus; Histochemistry; Ultrastructure